Altered BOLD response during inhibitory and error processing in adolescents with anorexia nervosa. - Christina Wierenga; Amanda Bischoff-Grethe; A James Melrose; Emily Grenesko-Stevens; Zoë Irvine; Angela Wagner; Alan Simmons; Scott Matthews; Wai-Ying Wendy Yau; Christine Fennema-Notestine; Walter H Kaye (PLoS ONE)
Background Individuals with anorexia nervosa (AN) are often cognitively rigid and behaviorally over-controlled. We previously showed that adult females recovered from AN relative to healthy comparison females had less prefrontal activation during an inhibition task, which suggested a functional brain correlate of altered inhibitory processing in individuals recovered from AN. However, the degree to which these functional brain alterations are related to disease state and whether error processing is altered in AN individuals is unknown. Methodology/principal findings In the current study, ill adolescent AN females (n = 11) and matched healthy comparison adolescents (CA) with no history of an eating disorder (n = 12) performed a validated stop signal task (SST) during functional magnetic resonance imaging (fMRI) to explore differences in error and inhibitory processing. The groups did not differ on sociodemographic variables or on SST performance. During inhibitory processing, a significant group x difficulty (hard, easy) interaction was detected in the right dorsal anterior cingulate cortex (ACC), right middle frontal gyrus (MFG), and left posterior cingulate cortex (PCC), which was characterized by less activation in AN compared to CA participants during hard trials. During error processing, a significant group x accuracy (successful inhibit, failed inhibit) interaction in bilateral MFG and right PCC was observed, which was characterized by less activation in AN compared to CA participants during error (i.e., failed inhibit) trials. Conclusion/significance Consistent with our prior findings in recovered AN, ill AN adolescents, relative to CA, showed less inhibition-related activation within the dorsal ACC, MFG and PCC as inhibitory demand increased. In addition, ill AN adolescents, relative to CA, also showed reduced activation to errors in the bilateral MFG and left PCC. These findings suggest that altered prefrontal and cingulate activation during inhibitory and error processing may represent a behavioral characteristic in AN that is independent of the state of recovery.